Freedom of Association and the Political Economy of Rights: The Collective Freedoms of Workers After SFL v. Saskatchewan - Smith, Charles W. (Studies in Political Economy, 2017)
In Saskatchewan Federation of Labour v. Saskatchewan (SFL v. Saskatchewan, 2015), the Supreme Court of Canada ruled that freedom of association in the Charter of Rights and Freedoms includes a collective ability for workers to strike. This decision was the latest in a series of cases in which the Supreme Court ruled that workers’ abilities to collectively bargain and strike are essential components of the constitutional protection of freedom of association. Using these decisions as a starting point, this paper reviews the uneven way that the court has elevated the associational freedoms of workers. The paper argues that the court’s balancing act between the collective freedoms of workers and the individual rights of employers conceals the material imbalance that has historically shaped capitalist social relations both inside and outside of the state. The paper argues further that these decisions have opened an important legal space for new mobilization strategies for working-class activists.
_eprint: https://doi.org/10.1080/07078552.2017.1342991
Keywords: Collective bargaining; Saskatchewan Federation of Labour v. Saskatchewan; Supreme Court of Canada; freedom of association; workers’ rights